Design, synthesis, and biological evaluation of a potent PLK4 inhibitor WY29 with 1H‐pyrazolo[3, 4‐d]pyrimidine scaffold. Issue 3 (28th November 2022) - Wang, Lin; Sun, Yu; Wang, Jingkai; Xue, Yanli; Sun, Yin; Qin, Qiaohua; Sun, Yixiang; Zhao, Dongmei; Cheng, Maosheng
Abstract: Centriole duplication occurs once per cell cycle and is regulated by Polo‐like kinase 4 (PLK4). Overexpression of PLK4 in somatic cells can lead to the excessive formation of centrioles, directly causing chromosome segregation errors and tumorigenesis. In this study, we described our efforts to develop a series of PLK4 inhibitors with 1 H ‐pyrazolo[3, 4‐ d ]pyrimidine core, and further structure‐ and receptor‐based design and optimization resulted in a potent inhibitor WY29 (IC50 = 0.027 μM), which exhibited good selectivity to other PLK family members (PLK1‐3). At the cellular level, compound WY29 showed excellent antiproliferative activity against three breast cancer cell lines (MCF‐7, BT474, and MDA‐MB‐231) while weak inhibitory activity was found on normal cell line HUVECs. In addition, the in vitro preliminary drug‐like properties evaluation of compound WY29 showed outstanding stability in human plasma and liver microsomes, and weak inhibitory activity against the major subtypes of human cytochrome P450. Also, the drug‐like properties prediction of compound WY29 displayed remarkable drug‐like properties (drug‐likeness mode score: 1.06). In conclusion, these results support the further development of compound WY29 as a lead compound for PLK4‐targeted anticancer drug discovery. Abstract : Starting from the hit compound WY01, a series of Polo‐like kinase 4 (PLK4) inhibitors with 1 H ‐pyrazolo[3, 4‐ d ]pyrimidine core was designed and synthesized. Among them, compounds WY29, WY30, and WY31 exhibited outstanding in vitro enzyme inhibitory activity. At the cellular level, compound WY29 showed high antiproliferative activity against three breast cancer cell lines but weak inhibitory activity on a normal cell line.